2017
DOI: 10.1177/0894439317715430
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Twitter’s Agenda-Building Power

Abstract: This study examined the relationship between elite news media agendas and campaign agendas during the 2016 presidential primary season. Computer-assisted content analysis was used to assess issue emphasis within Twitter feeds of U.S. presidential primary candidates and their campaigns as well as the nation's top newspapers. The relationship between the overall Twitter agenda and that of newspapers, as well as the influence of front-runners Clinton, Cruz, Sanders, and Trump, was investigated using time series a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 42 publications
(62 reference statements)
1
20
0
1
Order By: Relevance
“…One important characteristic of Twitter is that it allows politicians to directly influence the public's political agenda 16 . For example, as early as 2012, a sample of journalists acknowledged their reliance on Twitter to generate stories and obtain quotes from politicians 17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One important characteristic of Twitter is that it allows politicians to directly influence the public's political agenda 16 . For example, as early as 2012, a sample of journalists acknowledged their reliance on Twitter to generate stories and obtain quotes from politicians 17 .…”
mentioning
confidence: 99%
“…Relatively less attention has been devoted to the agenda-setting role of the tweets. Some research has identified the number of retweets Trump receives as a frequent positive predictor of news stories 22 (Though see 16 for a somewhat contrary position.). During the 2016 election campaign, Trump's tweets on average received three times as much attention than those of his opponent, Hillary Clinton, suggesting that he was more successful at commanding public attention 23 .…”
mentioning
confidence: 99%
“…For example, a 'symbiotic' relationship has been identified between Twitter feeds and top newspapers. Examining tweets from 2016 US presidential candidates and issue agendas in five US newspapers, it was found that tweets (e.g., on employment, immigration, national security) frequently predicted news agendas, and vice versa [38]. In another study, it was suggested Tweets can be used to infer voter preferences [39].…”
Section: Reactions To 'Trigger' Eventsmentioning
confidence: 99%
“…The intermedia agenda approach examines the ability to dictate the issues for the media agenda in its entirety and/or for the individual media outlets (Conway, Kenski, & Wang, 2015). The centrality of the social media, and Twitter in particular, has kindled a keen interest in its agenda-building role, spanning an interlinked continuum which ranges from the top-down dominance of the news media to bottom-up messaging in which the platform influences the agenda power of legacy media, while maintaining a reciprocal relationship (Conway, Filer, Kenski, & Tsetsi, 2017). Beyond the ability of one or another media outlet to set the agenda, the research focus is the convergence/divergence between the agenda of a platform like Twitter and that of the other media.…”
Section: The Public Agenda Between Legacy and Social Mediamentioning
confidence: 99%